The reinforcement learning workshop : learn how to apply cutting-edge reinforcement learning algorithms to your own machine learning models /: learn how to apply cutting-edge reinforcement learning algorithms to your own machine learning models. (2020) - Palmas, Alessandro; Ghelfi, Emanuele; Dr, Petre, Alexandra Galina; Kulkarni, Mayur; N.S., Anand; Nguyễn, Quân; Sen, Aritra; So, Anthony; Basak, Saikat
No abstract available